Clinical features of obsessive-compulsive disorder with hoarding symptoms: A multicenter study - Torres, Albina Rodrigues [UNESP]; Fontenelle, Leonardo F.; Ferrao, Ygor A.; Rosario, Maria Conceicao do; Torresan, Ricardo C.; Miguel, Euripedes C.; Shavitt, Roseli G. (Pergamon-Elsevier B.V. Ltd, 2012)
Background: Factor analyses indicate that hoarding symptoms constitute a distinctive dimension of obsessive-compulsive disorder (OCD), usually associated with higher severity and limited insight. The aim was to compare demographic and clinical features of OCD patients with and without hoarding symptoms.Method: A cross sectional study was conducted with 1001 DSM-IV OCD patients from the Brazilian Research Consortium of Obsessive-Compulsive Spectrum Disorders (CTOC), using several instruments. The presence and severity of hoarding symptoms were determined using the Dimensional Yale-Brown Obsessive-Compulsive Scale. Statistical univariate analyses comparing factors possibly associated with hoarding symptoms were conducted, followed by logistic regression to adjust the results for possible confounders.Results: Approximately half of the sample (52.7%, n = 528) presented hoarding symptoms, but only four patients presented solely the hoarding dimension. Hoarding was the least severe dimension in the total sample (mean score: 3.89). The most common lifetime hoarding symptom was the obsessive thought of needing to collect and keep things for the future (44.0%, n = 440). After logistic regression, the following variables remained independently associated with hoarding symptoms: being older, living alone, earlier age of symptoms onset, insidious onset of obsessions, higher anxiety scores, poorer insight and higher frequency of the symmetry-ordering symptom dimension. Concerning comorbidities, major depressive, posttraumatic stress and attention deficit/hyperactivity disorders, compulsive buying and tic disorders remained associated with the hoarding dimension.Conclusion: OCD hoarding patients are more likely to present certain clinical features, but further studies are needed to determine whether OCD patients with hoarding symptoms constitute an etiologically discrete subgroup. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Obsessive-compulsive disorder; Hoarding; Hoarding dimension; Hoarding symptoms; Clinical features; OCD subtypes